The partner myth: analysing the limitations of private sector contributions to the Sustainable Development Goals. Issue 7 (3rd October 2021) - Gneiting, Uwe; Mhlanga, Ruth
ABSTRACT : This viewpoint paper considers how companies are engaging in the Sustainable Development Goals (SDGs). Based on a review of the SDG engagement of 70+ of the world's largest companies, we challenge the assumption that business is making significant contributions to the SDGs. We develop an argument for how companies have continued with "business as usual" while reaping the reputational gains of being associated with the SDGs. We suggest four practices companies use to manage expectations to contribute to the SDGs (repackaging, cherry picking, agenda setting, and decoupling) and offer recommendations on how business can make more meaningful contributions to the SDGs.